Environmentally-literate citizenry among Malaysian youth to produce responsible environmental behaviour - Saiyidatina Balkhis Norkhaidi,; Hanifah Mahat,; Mohmadisa Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This quantitative study explores the environmentally-literate citizenry for responsible environmental behavior among Malaysian youth involving 1,000 young Malaysians selected from five regional zones (north, central, south, east coast, and East Malaysia). A stratified random sampling technique based on age gender and the location was used to select respondents. The study instrument was a questionnaire that involved two constructs; environmental literacy (atmosphere, hydrosphere, lithosphere, biosphere) and environmentally responsible behaviour. A descriptive analysis was used to represent level, frequency, and percentage. While Pearson correlation was used to find the relationship between environmental literacy and responsible environmental behaviour among Malaysian youth. Finding shows that the levels of environmental literacy at high levels (M = 4.050, SP = .611) and all sub-constructs also at high levels, atmosphere (M = 3.884, SP = .638), hydrosphere (M = 4.083, SP = .725), lithosphere (M = 3.964, SP = .683) and biosphere (M = 4.269, SP = .739). While responsible environmental behaviour was at a high average level with values of M = 3.868 and SP = .544. The correlation between environmental literacy and responsible environmental behaviour among Malaysian youth indicates a weak relationship strength (r=2.75, p=.000). Therefore, there show that environmentally will affect the literate citizenry among Malaysian youth to produce responsible environmental behaviour. It is hoped that this study will provide the basis for further research into the level and potential of literacy and environmentally responsible behaviour towards environmental sustainability in Malaysian society and increase awareness of serious environmental issues.